Pengaruh Kemiskinan dan Tingkat Pengangguran di Provinsi Aceh Terhadap Kesejahteraan Masyarakat Aceh - Budiyanto, Rizki; Putra, Mohammad Hafidz Fadhlurrahman; Lubis, Ade Abdillah Hafizh; Wokas, Hamida; Desmawan, Deris (Jurnal Informatika, 2024)
The purpose of this study is to see how poverty affects the welfare level of the people in Aceh Province. Poverty is a major problem that can hinder a country's economic and social progress. As an important part of Indonesia, poverty affects the welfare of people in Aceh Province. Secondary data collected from various credible sources was used for multiple linear regression data analysis. Per capita income level, education level, access to health services, and other factors that can affect people's welfare are the variables used in this study. According to the results of the analysis, poverty has a significant impact on people's welfare in Aceh Province. As a result, efforts to combat poverty should be increased by considering various components that can improve the overall quality of life of the people of Aceh. It is hoped that the results of this study will help policy makers create programs that will improve the welfare of the people of Aceh in a sustainable manner.